Human Rights By Any Other Name - Khalid, Azmi (Journal of Malaysian and Comparative Law, 2018)
From around the world, from countries of all the continents, they flock to the Alsatian city of Strasbourgh in France every summer. Each with a common purpose and a common passion - human rights. English - French - and Spanish-speaking individuals united by a common interest - to participate in the Study Session or the International Training Centre for University Human Rights Teaching ever since it was founded in 1968 by the recently-deceased Rene Cassin, winner of the Nobel Prize for Peace. Solemly they pay homage to his memory during the inaugural ceremony, attentively they listen to experts speak on various aspects of the subject, and fervertly they discuss and debate the problems faced throughout the world with the implementation of common standards to preseve the dignity of mankind. For four weeks they live and learn together, in mutual friendship which man-made frontiers had elsewhere split asunder, understanding and feeling diverse thoughts and minds, to return eventually to their own countries to spread the universal language of love and tolerance to all their peoples. A meagre milestone, no doubt, in the long and arduous endeavour to assert and reaffirm universal faith in fundamental human rights, but certaintly a constructive step in the right direction towards universal respect for this most valuable but, sadly, most violated asset of mankind. The activities and efforts of the Strasbourgh Institute form one of the few independent endeavours to concentrate on the legal study and training aspects of human rights development on an international basis. Western-oriented as it may seem to be under the sponsorship of UNESCO and the Council of Europe, its efforts are not to be similarly degraded to the level of political efforts of Western propaganda that might be alleged of some other institutions. Its eventual findings and results should not only vindicate its true aims but also finally benefit the international aim of promoting human rights everywhere. The purpose of this paper, written in the inspring atmosphere of internationalism during the 1976 sessions, is primarily to describe some major developments in the international protection of human rights, thereby making possible an evaluation of the importance of implementing human rights on a universal scale, notwithstanding its early origins, as well as a consideration of the necessary attitudes to ensure the success of that invalauble task. A tremendous idealistic task through it may appear to be, should individuals and governments everywhere pay serious attention to building up a human rights awareness and consciousness of a global nature, unsploit and unhindered by emotive feelings of parocbialism, ideology or pessismism, then there may yet be 'hope for the world'.